Flexible Supply Chain Network Design For CPO Derivatives - Andreasen Provicnius Chaidir (Institute of Computer Science (IOCS), 2020)
The crude palm oil (CPO) industry is one of the leading industrial sectors in Indonesia. The diversification of derivative products from the CPO refinery is very high (multi-product). The challenges of inefficiency in the distribution network of refined CPO products include multi-product, transportation distances, transportation costs, uncertainty in the supply chain, and traceability of products sent, volatile demand and having to adjust production volumes without incurring significant costs. actors and is a challenge that researchers also face. Therefore supply chain flexibility is a problem that arises in practice. The purpose of this research is to design a flexible supply chain network of CPO refinery products. Metaheuristic algorithm Genetic Algorithm (GA) is used in solving optimization challenges. Distribution network system entities are analyzed and then made into a mathematical form of Mixed Integer Linear Programming. Furthermore, the model was built with the help of the GA algorithm which was developed in the Java programming language using the MOEA Framework. The verification and validation of the model was carried out with a case study in the CPO refinery industry. The optimization results are evaluated for twelve periods to see the flexibility of the supply chain network design model that has been made the minimum cost for twelve simulation periods is Rp. 636,675,671 in the 9th period and the flexibility of the model for twelve periods is considered flexible because the model is able to meet demand with network utility above 100% in 8 simulation periods.